Public Relations Management Strategy to Counter Land Disinformation in the Multi-Stakeholder Project of Nusantara Capital City (IKN) - Ramadhana, Dhea Rizka; Christin, Maylanny (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study examines the public relations management strategy employed by the Nusantara Capital City Authority (OIKN) to counter land disinformation in Indonesia's multi-stakeholder capital relocation project. Using a qualitative descriptive-exploratory approach, the research involved purposive sampling of expert informants, key informants from OIKN and affected communities, and additional informants including journalists. Data collection employed in-depth interviews, participant observation, and document analysis, with findings analyzed using Miles and Huberman's three-stage approach and validated through triangulation methods. The study reveals that OIKN's public relations strategy demonstrates limited effectiveness, remaining predominantly reactive rather than preventive in addressing land disinformation. Key findings indicate significant communication gaps, including the absence of direct mandates for PR involvement in land regulation socialization, inadequate two-way communication channels, and geographic disparities in information distribution. The research identifies five primary obstacles hindering PR effectiveness: regulatory complexity, lack of direct PR mandates, one-way communication patterns, limited digital literacy and access, and institutional distrust due to insufficient transparency. Stakeholder perspectives from academics, affected residents, and media practitioners consistently emphasize the need for more proactive, inclusive, and transparent communication strategies. The study concludes that OIKN's current PR approach requires fundamental restructuring toward participatory dialogue facilitation, community-based communication, and strategic media partnerships to effectively manage disinformation and build public trust in large-scale development projects.